Dancing with eyes wide open: On the role of nostalgia in education. (28th November 2016) - Halpin, David
Abstract : Nostalgia rightly elicits suspicion, even derision, for to give oneself up to longing for something from the past runs the risk of compromising one's capacity to act effectively in the present. But this does not make nostalgia, by definition, either sentimentally reactionary or wistfully unreflective. On the contrary, in the education context and elsewhere, it can be the exact opposite, though its influence, which is legitimate, particularly when articulated through the optic of tradition, needs to be constrained and justified by good argument and, where relevant, sound empirical research.